Criminal guarantees victims of terrorism - الشمري منيف حواس (Journal of Legal Sciences, 2021)
Terrorist crimes mainly affect people lives in terms of physical integrity, the right to nproperty protection and other rights. This requires swift and immediate action to provide criminal protection for the victims of that crime. These procedures start from the moment the offense is completed. And here was the start in an attempt to pick up the pieces so as to shed light on the rights enjoyed by the victims of the terrorist crime starting from the moment it was committed until the implementation of the just retribution. Therefore, research on the rights of victims of terrorism is one of the reewable topics. This is what international efforts concerned with crime prevention and criminal justice have called and encouraged to draw the attention of the international community to the need to protect the rights of victims of terrorism, and to reduce the effective measures to reduce the pain and damage caused by the crime in order to enhance the national sense of security and safety. There is no doubt that the importance of such is still rising in the growing world, as the damages of terrorist crimes are more severe and have a greater impact than those committed in developed countries, which, with their wealth and high standards of living, could absorb many of the damages resulting from the crimes there